Aflatoxin B1 effects on the ovarian follicles of White Leghorn laying hens - HASANZADEH, S; SHAHROOZ, R; SADRKHANLOU, R (The Indian Journal of Animal Sciences, 2014)
The objective of this study was to investigate low dose and long duration effects of aflatoxin B1 on different categories of the ovarian follicles in adult White Leghorn layers. The birds were put in 2 groups, viz. experiment and as controls. Every chicken of experiment group was received AFB1 @ 0.62 ppm/day through oral route for the duration of 120 days. At the end of experiment, all the birds were slaughtered, immediately their ovaries collected and preserved in 10% buffered formaldehyde solution. In both the groups, the macroscopic follicles i.e. SWF, SYF, LYF (including F1, F2, F3, F4, F5), and POF were recorded, and then the specimens were subjected to tissue preparation, for histomorphologic and histomorphometric studies. All types of ovarian follicular distributions (including healthy and atretic) were recorded. There was highly significant (P<0.001) decrease in populations of SWF and SYF in test group. The reduction in different types of LYF as well as POF populations in test group were significant. There were high significant reduction in healthy microscopic and raise in atretic microscopic follicles in test group. It may be concluded that aflatoxin B1 in low dose (0.62 ppm/day) for the duration of 120 days causes increase in ovarian follicular atresia and death of different categories of the macroscopic as well as microscopic follicles in Leghorn layers.